Konsep Pendidikan Moral dan Etika dalam Perspektif Kristen - MariaLasfrida Silalahi; Susanna Jesica Barus; Iman Satria Ndururu; Maximilianus Wira (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
This paper attempts to portray the moral education of today's children froma Christianperspective. The term children today in Indonesia is better known as Kids Age Now. Kids AgeNow is actually a satire on the unnatural behavior of today's children. Moral education is a set ofbasic moral principles and the virtues of attitudes and character that must be owned and madeinto a habit by children from the time they are beginners until they become obedient to God. Inthe modern era, the problems that arise are physical and psychological problems. Physical problems lead to human conditioning as the object of all products of science and technology. This research is a library research (library research). This research collects text data. In this case, the author collects books, articles, internet data and journals that have relevance to the author'ssubject matter. To deal with the problems of Kids Age Now, what is needed is morals that aresourced from the Bible and Christian youth activities. Integration and interconnection betweenthe Bible and Christian youth activities, Science is a solution to create a moral life without losingthe progress of science itself. This will make today's children become children who are not outdated (science and technology) as well as children who have good morals and are commendable. People's perspective will also not view Kids Age Now as immoral children, but Kids Age Now who have good morals and are commendable. and excel in the advancement of science and technology